Respuesta :
[tex]f(x)=-2x+7\\\\g(x)=x^2-2\\\\\ [f\ \circ\ g](x)=-2(x^2-2)+7=-2x^2+4+7=-2x^2+11\\\\\text{Put x = 3 to the equation of the function}\\\\\ [f\ \circ\ g](3)=-2(3^2)+11=-2(9)+11=-18+11=-7\\\\Answer:\ \boxed{-7}[/tex]
Answer:
The value of [f o g](3) is -7
Step-by-step explanation:
Given two functions
[tex]f(x)=-2x+7, g(x)=x^2-2[/tex]
we have to find [f o g](3)
[tex]f(x)=-2x+7[/tex]
[tex][f o g](x)=f(g(x))=f(x^2-2)=-2(x^2-2)+7[/tex]
[tex][f o g](x)=-2x^2+4+7=-2x^2+11[/tex]
Put x=3
[tex][f o g](3)=-2(3)^2+11=-7[/tex]
The value of [f o g](3) is -7
Option 1 is correct